PENGARUH HARGA, CITRA MEREK DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA MULIA PRINT - Abyyu Nur Fahmi; Rio Sudirman; Rifka Arinda Noviasari (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to examine and analyze the Influence of Price, Brand Image, and Digital Marketing on Purchase Decisions at Mulia Print. The study was conducted at Jl. Mh. Thamrin No. 150A, Banyuwangi, with consumers of Mulia Print as the research sample. The sampling technique employed in this research is probability sampling, with a total of 40 samples. The method used in this study is quantitative, employing the distribution of questionnaires. Data analysis methods include instrument testing, multiple linear regression analysis, hypothesis testing, coefficient of determination testing, and classical assumption testing. Based on the analysis results, it was found that the calculated F value is greater than the tabulated F value (38.864 > 2.866), indicating that simultaneously, price (X1), brand image (X2), and digital marketing (X3) collectively influence purchase decisions (Y). In terms of individual variable analysis (t-test), the price variable showed a t value greater than the tabulated t value (4.501 > 2.028), leading to the conclusion that price influences purchase decisions. On the other hand, for the brand image variable, the t value was less than the tabulated t value (2.758 > 2.028), suggesting that brand image influences purchase decisions. Regarding the digital marketing variable, the t value was greater than the tabulated t value (1.926 > 2.028), leading to the conclusion that digital marketing does not significantly influence purchase decisions Key words: Price, Brand Image, Digital Marketing, Purchase Decisions